Uncovering Obstacles to Household Waste Recycling in Seremban, Malaysia through Decision-Making Trial and Evaluation Laboratory (DEMATEL) Analysis. - Zahari Md Rodzi; Ashiera Nadiha Hazri; Nurul Ain Syahirah Mohd Azri; Nurul Dania Farisha Sharul Rhmdan; Zati Aqmar Zaharudin; Saladin Uttunggadewa (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
This study investigates the barriers to household waste recycling in Seremban, Malaysia, using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) analysis. The research questions aimed to identify and rank the most significant barriers to recycling and understand the causal relationships between them. The study found that limited access to recycling facilities and services and lack of motivation or incentive to recycle were the most significant causes of household waste recycling barriers in Seremban. Onthe other hand, lack of motivation or incentive to recycle and negative attitudes towards recycling, were identified as the most significant effects. The study’s findings have theoretical implications for waste management and sustainable development and offer practical implications for policymakers and waste management practitioners in developing effective waste management strategies and policies that can address these barriers. Furthermore, the study’s insights into the most significant barriers to household waste recycling can inform the design of recycling campaigns and educational programs to increase awareness and promote household waste recycling in Seremban. Overall, this study provides a valuable contribution to the field of waste management and sustainable development and offers insights into the challenges of promoting household waste recycling in urban areas.